Polyclonal antibodies inhibit growth of key cellulolytic rumen bacterial species - Tondini, Sara M.; Mackie, Roderick I.; McCann, Joshua C. (Frontiers in Microbiology, 2023)
Antibodies targeting specific bacterial species could allow for modification of the rumen microbial population to enhance rumen fermentation. However, there is limited knowledge of targeted antibody effects on rumen bacteria. Therefore, our objective was to develop efficacious polyclonal antibodies to inhibit growth of targeted cellulolytic bacteria from the rumen. Egg-derived, polyclonal antibodies were developed against pure cultures of Ruminococcus albus 7 (anti-RA7), Ruminococcus albus 8 (anti-RA8), and Fibrobacter succinogenes S85 (anti-FS85). Antibodies were added to a cellobiose-containing growth medium for each of the three targeted species. Antibody efficacy was determined via inoculation time (0 and 4 h) and dose response. Antibody doses included: 0 (CON), 1.3×10-4 (LO), 0.013 (MD), 1.3 (HI) mg antibody per ml of medium. Each targeted species inoculated at 0 h with HI of their respective antibody had decreased (P < 0.01) final optical density and total acetate concentration after a 52 h growth period when compared with CON or LO. Live/dead stains of R. albus 7 and F. succinogenes S85 dosed at 0 h with HI of their respective antibody indicated a decrease (≥ 96%; P<0.05) of live bacterial cells during mid-log phase compared with CON or LO. Addition of HI of anti-FS85 at 0 h in F. succinogenes S85 cultures reduced (P<0.01) total substrate disappearance over 52 h by at least 48% when compared with CON or LO. Cross-reactivity was assessed by adding HI at 0 h to non-targeted bacterial species. Addition of anti-RA8 or anti-RA7 to F. succinogenes S85 cultures did not affect (P≥0.45) total acetate accumulation after 52 h incubation indicating that antibodies have less of an inhibitory effect on non-target strains. Addition of anti-FS85 to non-cellulolytic strains did not affect (P≥0.89) OD, substrate disappearance or total VFA concentrations providing further evidence of specificity against fiber-degrading bacteria. Western blotting with anti-FS85 indicated selective binding to F. succinogenes S85 proteins. Identification by LC-MS/MS of 8 selected protein spots indicated 7 were outer-membrane proteins. Overall, polyclonal antibodies were more efficacious at inhibiting growth of targeted cellulolytic bacteria than non-targeted bacteria. Validated polyclonal antibodies could serve as an effective approach to modify rumen bacterial populations.